The Republic in danger : Drusus Libo and the succession of Tiberius - Pettinger, Andrew (2012)
The volume proposes a new model for understanding the end of Augustus' reign and the succession of Tiberius in the years 6 BC to AD 16. Focusing on Drusus Libo's role in an alliance between the enemies of Tiberius, Pettinger offers a comprehensive analysis of the struggle between Tiberius and the supporters of Augustus' grandsons.